2018
DOI: 10.1007/s00038-018-1178-3
|View full text |Cite
|
Sign up to set email alerts
|

How do energy balance-related behaviors cluster in adolescents?

Abstract: Objective: To delineate the clustering of energy balance-related behaviors in adolescents, and investigate whether these behaviors are associated with the household socioeconomic status and parental education level. Methods: Two cross-sectional studies assessed information on sedentary behavior, physical activity, sugar-sweetened beverages and fruit and vegetable consumption, and sleep duration by self-reported questionnaires in adolescents (12.5-17.5 years old) from Maringá/Brazil (BRACAH study; n=682), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 41 publications
(46 reference statements)
1
22
0
1
Order By: Relevance
“…Cluster patterns were different by age, sex and SES in previous studies [14,16,17,23,36,37]. A higher proportion of girls, older children or adolescents, and children/adolescents from the lowest SES in the clusters de ned by low levels of PA, high levels of SB or high consumption of beverage drinking [14,20].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Cluster patterns were different by age, sex and SES in previous studies [14,16,17,23,36,37]. A higher proportion of girls, older children or adolescents, and children/adolescents from the lowest SES in the clusters de ned by low levels of PA, high levels of SB or high consumption of beverage drinking [14,20].…”
Section: Discussionmentioning
confidence: 80%
“…This implies a critical need to promote fruit and vegetable consumption among young adolescents. In previous studies, the majority of adolescents in Western countries also failed to meet guidelines for one or more health behavior(s); for example, high levels of screen time, low fruit and vegetable consumption, and inactivity tend to cluster in this age group [16,19,23]. Although there were differences in the numbers of health-related behaviors, measurements, analytical approaches and countries between the current study and other studies of adolescents, they consistently suggest that behavioral interventions to promote healthy behaviors are challenging, and more studies are required to promote a healthy lifestyle in adolescent population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although there has been a growing number of studies investigating the clustering or cooccurrence of multiple modifiable behaviors among adolescents, few of them were conducted in China [14][15][16][17][18][19][20][21][22][23]. Parker et al [14] systematically reviewed studies published up to May 2018, and identified 36 studies examining clusters of activity-related behaviors among adolescents, as well as socio-demographic characteristics and the modifiable correlates associated with behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the studies by Hyun-soo Kim (2018) and Farrell et al (2018) also identified gender differences in risk factors for suicide behaviours across diverse sample populations. In relation to other health outcomes, Moreau et al (2018) report higher prevalence of negative feelings about timing of first sexual intercourse among girls than boys in a European sample, Sadalla Collese et al (2018) found gender differences in clustering of energy-related behaviours among both Brazilian and European adolescents, and Paclikova et al (2018) found a moderating effect of gender on the relationship between family communication and emotional and behaviour problems in Slovak adolescents.…”
mentioning
confidence: 99%